Zeit, Raum, Figuren, Blick. Hermeneutische und methodische Grundlagen der Analyse biblischer Erzähltexte - Müllner, Ilse (Protokolle zur Bibel, 2006)
This paper gives a brief introduction to basic features of narrative which are at the same time central categories of narratology like time, space and character. In the 1990ies narratology has expanded its topic as well as questioned its hitherto mainly structuralist framework. Biblical Studies are extended between the probably not appropriate alternatives of literary and historical studies. Also biblical narrative seems to be both: literary work and - in quite a different way than the modern term would suggest - historiography. Narratology, if it sees itself as part of the cultural studies, can bridge this gap while still be rooted in literary criticism.